2005
DOI: 10.1111/j.1365-2141.2005.05779.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous prednisolone versus conventional prednisolone with VMCP–interferon‐α2b as first‐line chemotherapy in elderly patients with multiple myeloma

Abstract: SummaryWe report on a randomised trial that aimed to compare the efficacy of continued daily prednisolone treatment during the entire induction phase, with prednisolone given for 2 weeks of each cycle in combination with VMCP (vincristine, melphalan, cyclophosphamide, prednisolone)-interferon-a2b (IFN-a2b) treatment in 299 previously untreated elderly patients (median age: 67 years) with multiple myeloma. After completion of induction treatment patients were randomised to IFN-a2b with or without prednisolone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…[19][20][21] Among studies assessing the efficacy of the thalidomidebased regimens in untreated elderly patients with MM, the only one that is comparable to ours in terms of median age, exclusion criteria, and administered thalidomide dose is Palumbo et al, 13 who treated 129 patients with a combination of thalidomide, oral melphalan, and prednisone. With this regimen they observed combined CR and nCR in 28% of patients, near half the value that we obtained (48%).…”
Section: Discussionmentioning
confidence: 59%
“…[19][20][21] Among studies assessing the efficacy of the thalidomidebased regimens in untreated elderly patients with MM, the only one that is comparable to ours in terms of median age, exclusion criteria, and administered thalidomide dose is Palumbo et al, 13 who treated 129 patients with a combination of thalidomide, oral melphalan, and prednisone. With this regimen they observed combined CR and nCR in 28% of patients, near half the value that we obtained (48%).…”
Section: Discussionmentioning
confidence: 59%
“…The clinical trial showed similarity of the two treatment arms with respect to response rate, progression-free, and overall survival. Detailed results were published elsewhere (9). There was also no difference in outcome between patients taking or not taking part in the QOL sub-study.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety‐two patients participated in the QOL sub‐study of a trial comparing continuous vs. intermittent prednisolone in combination with VMCP–IFNα2b during induction, and IFNα2b with or without prednisolone twice weekly during maintenance in elderly patients with recently diagnosed multiple myeloma (9). Only patients with recently diagnosed, previously untreated multiple myeloma, ECOG performance status ≤3 and adequate organ function were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that psychosocial aspects of health‐related quality of life (HRQOL) provide independent prognostic information for survival, while the very few studies in patients with multiple myeloma found that physical and symptom focused HRQOL aspects provide independent prognostic information (4, 5). The results by Strasser‐Weippl and Ludwig are somehow limited, for example, they were not able to include cytogenetic data in the analysis, the research was conducted on a sub‐sample of 92 patients out of 299 enrolled in the original trial (6) and the issue of the possible harmful multicollinearity , which is relevant when using HRQOL scales of the EORTC QLQ‐C30, was not fully taken into account (7). Nevertheless, their results add to the scarce HRQOL literature in patients with hematological diseases and overall provide an important indication suggesting that what patients are telling us might indeed reveal important prognostic information, also in patients with hematological malignancies.…”
mentioning
confidence: 99%